Budget Perspectives 2013 - CALLAN, TIM (ESRI)
Welcome: Frances Ruane, Director, ESRI Macroeconomic Context for Budget 2013 David Duffy (ESRI) Fiscal Policy for 2013 and Beyond John FitzGerald (ESRI ) Benefit Integration in the UK: An Ex Ante Analysis of Universal Credit Mike Brewer (Institute of Social and Economic Research), James Browne and Wenchao Jin (Institute of Fiscal Studies) Work Incentives: New Evidence for Ireland Tim Callan, Claire Keane, Michael Savage, John R. Walsh and Kevin Timoney (ESRI)
PUBLISHED
Keywords: Economics